1979
DOI: 10.1530/jrf.0.0570235
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of alpha1-fetoprotein in fetal plasma, allantoic fluid, amniotic fluid and maternal plasma of cows

Abstract: Maximal concentrations of AFP, measured by RIA, were obtained in fetal plasma and amniotic and allantoic fluid between the 3rd and 4th month of gestation, with levels declining thereafter until term. AFP values in maternal plasma were unchanged. Throughout gestation, AFP values were higher in allantoic than in amniotic fluid and the ratio of allantoic fluid/amniotic fluid AFP was significantly correlated with gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
4
15
0
1
Order By: Relevance
“…Highly significant changes were observed in the concentrations of AFP, with relatively low values at birth and marked increase 1 day after colostrum intake. Smith et al (1979) have demonstrated that the concentrations of AFP in foetal bovine plasma reaches the highest values in the 3-4 th month of foetal period, which is followed by a significant decrease until birth. In our study, the mean concentration of AFP observed in calves at birth was only 0.453 μg/ml.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Highly significant changes were observed in the concentrations of AFP, with relatively low values at birth and marked increase 1 day after colostrum intake. Smith et al (1979) have demonstrated that the concentrations of AFP in foetal bovine plasma reaches the highest values in the 3-4 th month of foetal period, which is followed by a significant decrease until birth. In our study, the mean concentration of AFP observed in calves at birth was only 0.453 μg/ml.…”
Section: Discussionmentioning
confidence: 98%
“…Considerably higher values were reported by Yamada et al (1995) in newborn puppies at birth (14.08 mg/ml), which had fallen to 0.766 mg/ml at 1 week of age. A possible explanation for this difference is that the placentae in cows have more layers of tissue separating foetal and maternal blood than the placentae in other species (Smith et al 1979). Blohm et al (1998) the physiological effect on the foetal tissues changing from an intrauterine to an extrauterine environment with a decrease in the production of foetal proteins in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, several neoplastic cell lines of different ori gin have the property of incorporate AFP [27][28][29] and this incorporation occurs through specific membrane receptors [29][30][31][32], The developmental changes and tissue differences in AFP uptake could be ex plained if AFP receptors were also expressed by developing normal cells. In the case of serum albumin, several reports have de scribed the presence of albumin receptors in tissues such as heart [33], liver [34], white adipose tissue [34], kidney [35] and endothe lium [36], It is well known that AFP crosses the pla cental barrier from the fetus to the mother and is found in the maternal plasma during gestation [8,24,37], In an extensive study. Sell and Alexander [24] found that radiola belled AFP injected into pregnant rats also appeared in fetuses and that the half-life of radiolabelled AFP and albumin were consid erably lower in pregnant than in lactating or normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant of three fetus-specific proteins in cattle is ,-fetoprotein (Lai, Peters & Lorscheider, 1978), and the distribution of this protein has been reported in bovine fetal fluids from 42 days until full-term birth at 284 days (Smith, Lai, Robertson, Church & Lorscheider, 1979). Since methods are now available for the collection of pre-implantation embryos in cows (Church & Shea, 1977), the objectives of the present investigation were to establish the time of onset of AFP synthesis during early bovine embryogenesis, and specifically to determine whether implantation and placentation precede expression of the AFP gene.…”
Section: Introductionmentioning
confidence: 99%